2007
DOI: 10.1103/physreve.76.021902
|View full text |Cite
|
Sign up to set email alerts
|

Universal power law behaviors in genomic sequences and evolutionary models

Abstract: We study the length distribution of a particular class of DNA sequences known as 5'UTR exons. These exons belong to the messanger RNA of protein coding genes, but they are not coding (they are located upstream of the coding portion of the mRNA) and are thus less constrained from an evolutionary point of view. We show that both in mouse and in human these exons show a very clean power law decay in their length distribution and suggest a simple evolutionary model which may explain this finding. We conjecture tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(31 reference statements)
2
2
0
Order By: Relevance
“…Note that this distribution also presents linear regions in log-log scale [64]. A power-law-like distribution has been reported for 3′ untranslated regions earlier [82]. These findings, concerning the sizes of functional genomic sequence stretches, have to be the result of the action of mechanisms entirely different than the evolutionary scenario applied herein, as they extend in very short length scales (tenths to hundreds of nucleotides) while any random-aggregation procedure of the type proposed herein is unsuitable for the formation of functional sequence elements.…”
Section: Discussionsupporting
confidence: 78%
“…Note that this distribution also presents linear regions in log-log scale [64]. A power-law-like distribution has been reported for 3′ untranslated regions earlier [82]. These findings, concerning the sizes of functional genomic sequence stretches, have to be the result of the action of mechanisms entirely different than the evolutionary scenario applied herein, as they extend in very short length scales (tenths to hundreds of nucleotides) while any random-aggregation procedure of the type proposed herein is unsuitable for the formation of functional sequence elements.…”
Section: Discussionsupporting
confidence: 78%
“…Note that this distribution also presents linear regions in loglog scale [64]. A power-law-like distribution has been reported for 39 untranslated regions earlier [82]. These findings, concerning the sizes of functional genomic sequence stretches, have to be the result of the action of mechanisms entirely different than the evolutionary scenario applied herein, as they extend in very short length scales (tenths to hundreds of nucleotides) while any randomaggregation procedure of the type proposed herein is unsuitable for the formation of functional sequence elements.…”
Section: Evolutionary Origin and Implications Of Cne Chromosomal Distributionssupporting
confidence: 78%
“…We design a statistical model to estimate the probabilities of fragments which are a part of the novel transcript. It is reported that the distribution of mouse exon lengths shows a very clean power law decay [ 18 ]. With this theory, we select potential fragments by validating the distribution of mouse transcript and calculating the cumulative distribution function.…”
Section: Resultsmentioning
confidence: 99%